Executive Committee Minutes 2020-08-20 - Academic Senate:::::::::
Welcome. Approval of Agenda – item added: Appointment of Carmen Works as Past Chair for AY 20-21. Approved. Approval of Minutes of 5/7 and 6/4 – Approved. Chair Report. President Report. Working group for online education policy/procedures discussion. Provost Report. Statewide Senator Report. Carmen Works appointment as Past Chair. Senate Agenda approved. Vice President of Administration and Finance Report. VP for Student Affairs report. Associated Students Report.